Tsunamis and geophysical warnings - Hunt, J; Kopec, G; Aplin, K (2010)
Meeting report Julian Hunt, Grant Kopec and Karen Aplin report on new techniques and practical approaches before, during and after devastating events such as tsunamis. © 2010 Royal Astronomical Society.